Garis panduan menamai syarikat, bangunan, kawasan perumahan, tempat awam, dan jalan. - Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1996)
How to name corporations, housing, public spaces, and roads in Malaysia.
Includes bibliographical references : (p. 107-108).
In Malay.
Keywords: Business names -- Malaysia; House names -- Malaysia; Names, Geographical -- Malaysia; Street names -- Malaysia